Nonpoint source pollution by swine farming wastewater in bean crop Poluição difusa da água residuária de suinocultura do feijoeiro - André F. Doblinski; Silvio C. Sampaio; Vanderlei R. da Silva; Lúcia H. P. Nóbrega; Simone D. Gomes; Tatiane C. Dal Bosco (Revista Brasileira de Engenharia Agrícola e Ambiental)
In order to verify the environmental impact of the application of swine farming wastewater in bean crop, an experiment was set up in the Experimental Farm of PUCPR - Toledo, PR, Brazil. Runoff and soil samples were collected at the end of the experiment. Four wastewater treatments were utilized during the experiment (50, 100, 150 and 200 m³ ha-1) and the without wastewater as the control. The results demonstrate that (i) the amounts of potassium, phosphorus, and nitrogen in runoff are exponential, (ii) that phosphorus has a seven-fold polluting potential compared to potassium and three-fold compared to nitrogen, and (iii) that the mobility of potassium in the soil profile is the largest, followed by those of nitrogen and phosphorus. Visando verificar o impacto ambiental da aplicação de água residuária de suinocultura na cultura do feijoeiro, instalou-se um experimento na Fazenda Experimental da PUCPR - Toledo, PR, Brasil; para isto, amostras do solo e do escoamento superficial foram coletadas ao final do experimento e se utilizaram quatro taxas de aplicação de água residuária durante o experimento, 50, 100, 150 e 200 m³ ha-1, sem aplicação de água residuária como testemunha. Os resultados demonstraram que: (i) as perdas de potássio, fósforo e nitrogênio no escoamento superficial são exponenciais; (ii) o fósforo apresenta potencial poluidor sete vezes maior que o potássio e três vezes maior que o nitrogênio; (iii) a mobilidade do potássio no perfil do solo é maior, seguida do nitrogênio e do fósforo.